2017
DOI: 10.1002/mc.22666
|View full text |Cite
|
Sign up to set email alerts
|

Non‐digestible carbohydrates supplementation increases miR‐32 expression in the healthy human colorectal epithelium: A randomized controlled trial

Abstract: Colorectal cancer (CRC) risk is modulated by diet and there is convincing evidence of reduced risk with higher non‐digestible carbohydrates (NDCs) consumption. Resistant starch (RS), a NDC, positively modulates the expression of oncogenic microRNAs, suggesting that this could be a mechanism through which NDCs protect against CRC. The present study aimed to investigate the effects of supplementation with two NDCs, RS, and polydextrose (PD), on microRNA expression in the macroscopically‐normal human rectal epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In line with the in vivo data, mutations and deletions of TRAF3 are detected in 2.3% (10/439) of human colon cancers (TCGA, PanCancer Atlas). Furthermore, miR-32-TRAF3-mediated inhibition of the NIK-NF-κB2 pathway protects human colorectal epithelium against colorectal cancer in response to a diet of non-digestible carbohydrates ( 181 ). Thus, TRAF3 appears to act in both epithelial cells and myeloid cells to suppress colon tumorigenesis by inhibiting the NF-κB2 and TLR-induced inflammatory pathways.…”
Section: Traf3mentioning
confidence: 99%
“…In line with the in vivo data, mutations and deletions of TRAF3 are detected in 2.3% (10/439) of human colon cancers (TCGA, PanCancer Atlas). Furthermore, miR-32-TRAF3-mediated inhibition of the NIK-NF-κB2 pathway protects human colorectal epithelium against colorectal cancer in response to a diet of non-digestible carbohydrates ( 181 ). Thus, TRAF3 appears to act in both epithelial cells and myeloid cells to suppress colon tumorigenesis by inhibiting the NF-κB2 and TLR-induced inflammatory pathways.…”
Section: Traf3mentioning
confidence: 99%
“…We have shown that in the macroscopically normal colorectum of healthy participants, supplementation with non‐digestible carbohydrates (a source of butyrate) for 7 weeks significantly increased the expression of miR‐32 , involved in the regulation of cell proliferation levels (Malcomson et al . 2017b). Furthermore, resistant starch significantly reduced the expression of CTNNB1 and c‐MYC , as well as SFRP1, suggesting further protective effects of dietary fibre via effects on WNT signalling (Malcomson et al .…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, TRAF3 can be regulated by various miRNAs. For example, TRAF3 has been demonstrated to be targeted by miR-32 to affect non-canonical NF-κB signaling and consequently, NIK stabilization (52). TRAF3 is also directly targeted by miR-214-3p to promote osteoclast-and bone-resorbing activity (53).…”
Section: Discussionmentioning
confidence: 99%